2011
DOI: 10.1111/j.1601-0825.2011.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

HCMV gB genotype and its association with cytokine levels in hematopoietic stem cell transplantation

Abstract: Decreased IL-1β and increased IL-10 levels in the blood are associated with lower survival. HCMV genotypes are associated with different cytokine levels in saliva and blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Among viral factors, genetic variability has been analyzed in order to determine the possible association between viral genetic features and infection outcome; several genes have been targeted for evaluation including those encoding for gB, glycoprotein N, glycoprotein O, and the UL144 gene, among others [6,11,12,13,14]. The gB gene has been studied in different risk groups, including both solid organ and hemopoietic transplant patients [5,15,16,17,18,19,20,21,22,23,24,25,26,27], HIV-infected patients [4,6,15,16,28,29,30,31,32,33], infants with congenital infection [3] and healthy subjects [34]. So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among viral factors, genetic variability has been analyzed in order to determine the possible association between viral genetic features and infection outcome; several genes have been targeted for evaluation including those encoding for gB, glycoprotein N, glycoprotein O, and the UL144 gene, among others [6,11,12,13,14]. The gB gene has been studied in different risk groups, including both solid organ and hemopoietic transplant patients [5,15,16,17,18,19,20,21,22,23,24,25,26,27], HIV-infected patients [4,6,15,16,28,29,30,31,32,33], infants with congenital infection [3] and healthy subjects [34]. So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results. Nevertheless, it appears that in certain circumstances strain type may have a role in the occurrence of CMV disease; for instance, most studies in HIV-positive patients report gB2 as the most common genotype [4,6,15,16,28,29,30,31,32,33], while in transplant patients gB1 is the predominant genotype [5,15,16,17,18,19,20,21,22,23,24,25,26,27]. Also, the interpretation of these results is affected by the frequent detection of coinfections with two or more CMV strains in immunosuppressed patients [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have spiked the interest of clinical virologists in identifying potential correlations between genetic variants and the pathogenic potential of different isolates. Several studies have found some evidence to correlate specific genotypes with disease outcome, investigating polymorphisms in the UL55 (glycoprotein B) (16)(17)(18)(19), UL73 (glycoprotein N) (20)(21)(22), UL75 (glycoprotein H) (23), UL144 (tumor necrosis factor alpha [TNF-␣]-like receptor) (24)(25)(26), and UL146 and UL147 (viral CXCL chemokines) (27,28) genes. Others, however, found no evidence of these relationships (29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Variation in gB has been used to classify HCMV genotypically, and may influence the clinical outcome (21,22), probably by affecting the cell and organ tropism of HCMV (23), the virulence of different strains (24), and host lymphocyte subpopulations and cytokine levels (25). In contrast, a lack of correlation between gB types and clinical outcomes (26-28) or a response to therapy (29) has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent intragenic variation in gB and infection with multiple gB subtypes have rendered breakthroughs in the diagnosis, treatment, or prevention of HCMV infection problematic. Moreover, reinfection and multiple infections with HCMV gB subtypes occur, and this is thought to result in an unfavorable prognosis (25,30). An ELISA (31) has been reported to detect strain-specific antibody responses using recombinant antigens based on polymorphic antibody binding sites in gH (glycoprotein H) and gB from the Towne and AD169 strains.…”
Section: Discussionmentioning
confidence: 99%